The Uncanniness of Intermediality. Joanna Hogg’s Eerily Self-Reflexive Cinema - Pethő Ágnes (Acta Universitatis Sapientiae: Film and Media Studies, 2023)
The article argues for the relevance of the concept of the uncanny for a nuanced approach of intermediality. It identifies specific areas where the uncanniness of intermediality appears and examines Joanna Hogg’s three autobiographically inspired films, The Souvenir (2019), The Souvenir Part II (2021), and The Eternal Daughter (2022) from this point of view. The analysis does not offer a psychoanalytic reading of these films but focuses on aesthetic configurations that enable the affective performativity of intermediality in conjunction with particular strategies of reflexivity, and unravels the ways in which, ultimately, all these films speak about the uncanny, mutually haunting relationship between art and life. Blurring the line between fiction and nonfiction, Hogg depicts the paradoxical nature of (post)trauma and the emotional turmoil of mourning feeding into artistic creativity. The Souvenir films revolve around the loss of a lover in her youth and weave together different styles and resonances across art history and many mediums. They reveal memory, imagination and palpable reality folding over in an uncanny and aestheticized construction of space and time. The Eternal Daughter presents a scenario of caring for her dying mother, and brings to the fore the tropes of the haunted house, ghosts and doubles, which were latent figures of the earlier films as well.1